Analyzing Greece 2010 memorandum's impact on macroeconomic and financial figures through FCM - Stavros P. Migkos; Damianos P. Sakas; Nikolaos T. Giannakopoulos; Georgios Konteos; Anastasia Metsiou (Economies, 2022)
The financial crisis of 2008 has caused a series of drawbacks to economies around the world. Greek economy has been hit twice at 2009, since its credibility worsened, provoking the implication of harsh fiscal measures from the 2010 Memorandum of Understanding (MoU). The effects of these measures to Greek macroeconomic figures have been widely criticized. Authors aim to estimate these effects at the macroeconomic figures of Greece through utilization of Decision Support Systems, and propose accurate insights regarding their efficacy. By capitalizing on regression analysis and Fuzzy Cognitive Mapping processes, specific results from 2010 Memorandum's measures arise. It has been calculated that measures implied by 2010 Memorandum have been harsh and posed a negative effect on key Greek macroeconomic figures like GDPR, public debt, etc., especially with the ongoing 2008 financial crisis.
Keywords: 330; 2010 memorandum; decision support systems; financial crisis; fuzzy cognitive mapping; macroeconomics; monetary policy; regression analysis